ORGANIZATION OF SAFE MANAGEMENT OF FIRE OPERATIONS ON GAS PIPELINES - Abdrakhmanov N. Kh.; Fedosov A. V.; Shaibakov R. A.; Abdrakhmanova K. N.; Sharipov (Aubakirov) G. A.; Kozlowski Waldemar (Scientific Journal of Pedagogy and Economics, 2019)
The article discusses the issues of safe operations on the main gas pipelines of the Republic of Kazakhstan, which, as a result of deterioration of pipelines main part and their active susceptibility to stress corrosion cracking, require repair work. Considered new approaches of repair work organization by open fire using. It has been analyzed that the application of these measures in practice will ensure proper organizational planning and technical training of personnel, and effective provision of necessary level safety for hot work. It was concluded that it is necessary to introduce safety increasing measures during fire work on gas pipelines, it will prevent possible disasters, fires, destruction and human losses due to explosions during repair work on gas pipelines, as well as reduce damaging factors affecting workers health. It is shown that introduction of the named above measures helps to prevent disasters, fires, destruction and loss of life as a result of explosions during gas pipelines repair, as well as damaging factors reduction that affect workers health during these types of work.